Arylative Intramolecular Allylation of Ketones with 1, 3‐Enynes Enabled by Catalytic Alkenyl‐to‐Allyl 1, 4‐Rhodium(I) Migration. (19th May 2017) - Partridge, Benjamin M.; Callingham, Michael; Lewis, William; Lam, Hon Wai
Abstract: Alkenyl‐to‐allyl 1, 4‐rhodium(I) migration enables the generation of nucleophilic allylrhodium(I) species by remote C−H activation. This new mode of reactivity was employed in the diastereoselective reaction of arylboron reagents with substrates containing a 1, 3‐enyne tethered to a ketone, to give products containing three contiguous stereocenters. The products can be obtained in high enantioselectivities using a chiral sulfur‐alkene ligand.